2017
DOI: 10.1111/cdev.12909
|View full text |Cite
|
Sign up to set email alerts
|

Specific Preschool Executive Functions Predict Unique Aspects of Mathematics Development: A 3‐Year Longitudinal Study

Abstract: This study assessed the extent to which executive functions (EF), according to their factor structure in 5-year-olds (N = 244), influenced early quantity-number competencies, arithmetic fluency, and mathematics school achievement throughout first and second grades. A confirmatory factor analysis resulted in updating as a first, and inhibition and shifting as a combined second factor. In the structural equation model, updating significantly affected knowledge of the number word sequence, suggesting a facilitato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 42 publications
3
22
1
Order By: Relevance
“…We measured EF in 4.5-to 5.5-year-old children, given the significance of this period for school readiness (e.g., Morgan et al, 2018). Further, given that EF by these ages is multidimensional (Monette, Bigras, & Lafrenière, 2015;Simanowski & Krajewski, 2017), we assessed multiple aspects of EF including sustaining attention, inhibitory control, and working memory, which in this paper is defined as holding information in mind (Luck & Vogel, 1997;Riggs, McTaggart, Simpson, & Freeman, 2006;Simmering, 2012). Parental depression and parenting stress were assessed as measures of parental well-being.…”
Section: Current Studymentioning
confidence: 99%
“…We measured EF in 4.5-to 5.5-year-old children, given the significance of this period for school readiness (e.g., Morgan et al, 2018). Further, given that EF by these ages is multidimensional (Monette, Bigras, & Lafrenière, 2015;Simanowski & Krajewski, 2017), we assessed multiple aspects of EF including sustaining attention, inhibitory control, and working memory, which in this paper is defined as holding information in mind (Luck & Vogel, 1997;Riggs, McTaggart, Simpson, & Freeman, 2006;Simmering, 2012). Parental depression and parenting stress were assessed as measures of parental well-being.…”
Section: Current Studymentioning
confidence: 99%
“…In addition, although some previous studies have shown that earlier EF predicts future number competence (e.g., Kolkman et al, 2013 ; McClelland et al, 2014 ; Purpura et al, 2017 ), little is known about whether EF continues to predict mathematics skills after controlling for number competence such as number sense. Fuhs et al (2016) , for example, found that the effects of early EF on concurrent mathematics performance were fully mediated by number sense, and Simanowski and Krajewski (2017) also found that EF in kindergarten could not predict mathematic skills in Grades 1 and 2 (mean ages were 87 and 99 months, respectively) after controlling for early number competence. Therefore, as Viterbori et al (2015) have suggested, children’s number sense should be controlled before examining the contribution of EF subcomponents to mathematics skills.…”
Section: Introductionmentioning
confidence: 99%
“…Second, most previous studies examining the relationship between EF and mathematics are cross-sectional (e.g., Agostino et al, 2010 ; Rose et al, 2011 ; Cantin et al, 2016 ). The few longitudinal studies (e.g., Swanson, 2006 ; McClelland et al, 2014 ; Simanowski and Krajewski, 2017 ; Vandenbroucke et al, 2017 ) have covered only a limited developmental span (most often from Kindergarten to Grades 1 and 2) and have used the EF skills (assessed at an earlier point in time) to predict mathematics skills at a later point in time (often assessed once). To our knowledge, only a handful of longitudinal studies have examined how EF predicts different growth parameters (intercept and slope) in mathematics (see Bull et al, 2008 ; Geary, 2011 ; van der Ven et al, 2012 ; Van de Weijer-Bergsma et al, 2015 ; Lee and Bull, 2016 ), and of these studies only two had assessed all three EF subcomponents ( Bull et al, 2008 ; van der Ven et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Working memory (WM). Improvement in working memory (also known as updating; Simanowski & Krajewski, 2019) between ages 3 and 5 years is documented for digit or word span tasks (e.g., Espy & Bull, 2005), spatial or object span tasks (e.g., Ewing-Cobbs et al, 2004), spatial and object memory (e.g., Ewing-Cobbs et al, 2004), and tasks that assess the ability to track and update a number of items (e.g., Hongwanishkul et al, 2005).…”
mentioning
confidence: 99%
“…Mathematics skills (usually numeracy) and EF develop throughout the preschool years (e.g., Purpura, Schmitt, & Ganley, 2017;Schmitt et al, 2017;Wolf & McCoy, 2019) and influence a child's academic achievement in kindergarten and into grade school (e.g., Nesbitt, Fuhs, & Farran, 2019;Nguyen & Duncan, 2019;Simanowski & Krajewski, 2019). Few significant pre-k gender differences are reported in mathematics performance (Corrington, 2008;Ganley & Lubienski, 2016), and upon kindergarten entry, girls score the same as boys (Robinson & Lubienski, 2011) or higher (Corrington, 2008).…”
mentioning
confidence: 99%